THE LEVELS OF SEWERAGE SYSTEM PERFORMANCEIN ARD ZWAWA ALBAHRIA, BENGHAZI CITY,LIBYA - Taher, Hamza Hassan; Suprapto, Mamok; Astuti, Winny (Jurnal Teknik Sipil, 2014)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â Sewer systems are prone to damages due to aging, traffic, geological change, to name a few. The sewer system is very important in the life and any malfunction in a sewer system disrupts the daily life activities within the relevant region. This research is proposed some solution in order to the assessment of the level to performance the sewage network in Ard Zwawa Albahria, East Benghazi City. There are many problem in Ard Zwawa Albahria sometimes flood and also close to some of manholes.The objectives of this research are to observe and to analysis the levels of sewerage system performance in Ard Zwawa Albahria, East Benghazi City- Libya and the effect of the systemâs performance to the decision making process for rehabilitation and maintenance. Using performance Indices and Standard of Scoring Matric, this research uses some formulas for calculation to evaluate the components of sewage system based on standard called Libyan specifications. The level of sewage system performance is 3.29 .it means that the sewage system is in a good condition. The system only needs rehabilitation and maintenance. The spatial coverage of existing sewers system is not good enough, because there are some places which donât have network of sewer system. The general capacity of sewage system network is good enough, because it can service the quantity of flowing sewage water. The length of pipe equals 3984.27 meterKeywords: performance indices ,sewerage system, infrusrauction, level of assessment .